SELECTIVITYBOTTOM GILLNET AT DESA NARAS 1 KECAMATAN PARIAMAN UTARA PARIAMAN CITY PROVINSI SUMATERA BARAT - Maisuri Dewi; Alit Hindri Yani; Nofrizal Nofrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRAKPariaman City is a coastal and marine area, where fish products have an important role in the economic cycle, one of which is in Naras Village 1. This study aims to determine the selectivity of mesh size on the composition and size of catches on gill net. The method used in this study is experimental fishing, a method that uses a sample of objects to be observed. The results of this study indicate that there are 9 species of fish caught on a mesh size of 1.5 inch and 1.75 inch,kurisi (Nemipterus hexodon), barakuda (Sphyraena barracuda), mojjaras (Eucinostomus),selar kuning (Selaroides leptolepis), beloso (Saurida tumbill), parang-parang (Chirocentrus nudus), kembung (Rastrelliger spp), tenggiri (Scomberomorus commersoni), and kaci-kaci (Painted sweetlips). Dominant fish caught in both mesh sizes are 320 fish kurisi or 41% of the total catch, with a total length of 13.5 - 25.7 cm, fork length 11.5 - 23.2 cm, height 3 , 2 - 5.6 cm and weigh 40 - 170 g. Difference in mesh size that is not too large only gives a slight effect both on the total number of catches and the average fork length of fish caught. The most selective basic gill nets are gill nets with a mesh size of 1.75 inches, this is because the mesh size of 1.75 inches only catches large-sized fish that are worth catching and can pass small fish. Keywords: selectivity, bottom gillnet, fish kurisi,naras 1 village.